2021
DOI: 10.1007/s12186-021-09267-3
|View full text |Cite
|
Sign up to set email alerts
|

Informal Workplace Learning in Swedish Police Education– A Teacher Perspective

Abstract: In the literature, informal learning is considered to be of great importance to employees’ development of workplace learning. The aim of this study, which involves respondents from a Swedish police education unit, was to contribute knowledge about Swedish police education teachers’ informal learning as regards conditions for learning, learning activities and learning experiences resulting from their engagement in these activities. The results of the study are based on daily digital logbook notes made by 25 pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…In light of the demands made in recent years for increased professionalisation (Basham, 2014; Shipton, 2019) in both police organisations (Filstad et al , 2020) and police education and training (Bergman and Karp, 2020), the results of this study suggest that an organisational structure, where favourable conditions for the integration of police-specific and academic knowledge are provided (Author 2 and Author 1, 2021), benefit teachers’ professional development. The study’s findings also show clear indications of a ripple effect as more and more teachers seem to be involved in informal learning activities, which contributes to the development of the police educations’ subject content and teaching arrangements.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In light of the demands made in recent years for increased professionalisation (Basham, 2014; Shipton, 2019) in both police organisations (Filstad et al , 2020) and police education and training (Bergman and Karp, 2020), the results of this study suggest that an organisational structure, where favourable conditions for the integration of police-specific and academic knowledge are provided (Author 2 and Author 1, 2021), benefit teachers’ professional development. The study’s findings also show clear indications of a ripple effect as more and more teachers seem to be involved in informal learning activities, which contributes to the development of the police educations’ subject content and teaching arrangements.…”
Section: Discussionmentioning
confidence: 79%
“…The interviews were part of a larger data collection, which also included logbooks. This study is part of a larger project, where a previous focus was on the conditions for the teachers' informal workplace learning and the informal learning activities that emerged (Sjöberg and Holmgren, 2021). Thus, the interview material on which this article is based should be seen as a part of the teachers' overall narratives dealing with the conditions for their involvement in informal learning activities, the motives (triggers) behind their engagement, and their interaction with human and material resources at work.…”
Section: The Materials Usedmentioning
confidence: 99%
“…Previous research on how teachers learn the simulation practice has not been found in the literature reviews conducted for this paper. However, the findings of this study are connected to research on informal workplace learning and how professionals mostly learn, i.e., informally by dealing with challenges that occur in their everyday work, rather than through formalised learning (see Billet, 2004;Boud & Hager, 2012;Sjöberg & Holmgren, 2021). In line with previous research, this study shows that professional Sjöberg development at work is characterised by its social and collaborative nature, which includes sharing of knowledge in the workplace and reflections on actions performed (Boud & Rooney 2018;Sjöberg & Holmgren, 2021;Tynjälä, 2008).…”
Section: Rq2: How Do Police Teachers Develop Their Simulation Exercisesmentioning
confidence: 81%
“…Being a competent teacher therefore implies a good knowledge of the subject matter and of how things are done and arranged at their workplace (see Boud & Hager, 2012). Teachers' informal learning in a police education context was the focus of two studies (Sjöberg & Holmgren, 2021;Holmgren & Sjöberg, 2022), which reported on the value that police teachers placed on informal learning activities and how central such activities are, both for their professional development and for the development of their teaching practice. The teachers described a professional transformation from instructor to a teacher with more pedagogical knowledge that took place over time.…”
Section: Professional Development Of Teachersmentioning
confidence: 99%
“…Informal learning takes place both within individual activities, such as reading and analyzing professional literature, establishing social contacts with other professionals in one's own or another field and observing the performance of other professionals, and within collective activities such as mentoring or involvement in professional networks (Desimone, 2009). Informal learning provides greater flexibility and freedom for participants as opposed to a formal learning process, emphasizes the need and offers the opportunity to learn from other professionals, and takes place in various forms and allows the employee to update and use the professional experience accumulated within the organization (Sjöberg & Holmgren, 2021).…”
Section: Previous Findingsmentioning
confidence: 99%